2002
DOI: 10.1161/01.atv.0000022167.80130.a6
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Effect of Androgens on Serum Inflammatory Markers in Men

Abstract: Objective-Because male sex is an independent risk factor for the severity of atherosclerosis, it is possible that androgens may be proatherogenic. There is evidence that sex hormones, particularly estrogens, regulate (or modulate) inflammation, a process integral to atherogenesis. Because levels of serum inflammatory markers predict cardiovascular outcomes, we prospectively assessed the effects of androgen therapy on these markers in older men. Methods and Results-Levels of high-sensitivity C-reactive protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 42 publications
(47 reference statements)
4
50
1
1
Order By: Relevance
“…Others have similarly found no effect on IL-6 levels with testosterone therapy (29). Two studies in healthy men have found no effect of androgen therapy on CRP (50,51). Both these studies, similar to the present study, were short-duration studies over 3-6 months and the long-term effect of testosterone treatment on CRP has not been investigated.…”
Section: Discussionsupporting
confidence: 63%
“…Others have similarly found no effect on IL-6 levels with testosterone therapy (29). Two studies in healthy men have found no effect of androgen therapy on CRP (50,51). Both these studies, similar to the present study, were short-duration studies over 3-6 months and the long-term effect of testosterone treatment on CRP has not been investigated.…”
Section: Discussionsupporting
confidence: 63%
“…Testosterone has innate immune modulating properties [19]. There is, also, evidence that testosterone reduces inflammation and reduces inflammatory cytokines [16,20]. Hypogonadal or eugonadal men suffering with chronic inflammatory diseases have been shown to improve following testosterone administration [17,21].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a similar study demonstrated that testosterone therapy had no effect on serum TNFa concentrations in men with chronic heart failure (Pugh et al 2005) and testosterone replacement in hypogonadal men with T2DM had no effect on the TNFa, IL6 or CRP levels (Kapoor et al 2007). Likewise, in a prospective study of older men, the administration of DHT or human chorionic gonadotrophin (to stimulate testosterone synthesis from the Leydig cells) did not significantly alter the highsensitivity CRP, soluble vascular cell adhesion molecule 1 (sVCAM-1) or soluble intracellular adhesion molecule (sICAM) levels (Ng et al 2002).…”
Section: Testosterone and Vascular Inflammationmentioning
confidence: 94%